Unnatural amino acid mutagenesis-based enzyme engineering. Issue 8 (August 2015) - Ravikumar, Yuvaraj; Nadarajan, Saravanan Prabhu; Hyeon Yoo, Tae; Lee, Chong-soon; Yun, Hyungdon
Highlights Enzyme engineering using in vivo incorporation of unnatural amino acids (UAA). Enhancing and altering enzyme activity using residue- and site-specific incorporation of UAA. Enzyme evolution with UAA by integrating directed evolution and UAA incorporation.